Social work and social problems: A contribution from systems theory and constructionism. (8th April 2014) - Michailakis, Dimitris; Schirmer, Werner
<x xml:space="preserve">Abstract</x> Social work builds its identity on social problems. The goal is to generate knowledge about causes, consequences and solutions. However, there is a lack of theory of social problems. We suggest that research on social problems can benefit by 'bringing the observer in': Loseke's constructionist framework and Luhmann's systems theory. According to Loseke, social problems appear differently when constructed by different observers. Constructions vary in terms of morality, conditions, victims/villains and solutions. From Luhmann we learn that modern society consists of a multitude of social systems (e.g. politics, science, economy etc.), each operating with their own communicative codes. Combining both approaches, we hypothesise that any social system constructs its own (version of) social problems. Illustrating with the empirical case 'suicide among mentally ill people', we examine how a phenomenon is constructed differently as a social problem by four different social systems: the disability movement, politics, medicine and social work.